تطبيقات البيانات الضخمة والاقتصاد الرقمي –عرض تجارب دولية رائدة - دوبابي, أحلام; بالمهدي, نور الهدى (University of Eloued جامعة الوادي, 2022)
تهدف هذه الدراسة إلى التعريف بالبيانات الضخمة ا ولاقتصاد الرقمي وتطور تقنياته على المستوى الإقليمي والدولي في ظل الثورة الرقمية والتحول الرقمي الذي يشهده العالم, واستعراض بعض التجارب الدولية الناجحة في تبني الاقتصاد الرقمي واستخدام البيانات الضخمة لاسيما في فترة الأزمة الصحية لجائحة كوفيد- 19 ، وقد تم الاعتماد على المنهج الوصفي التحليلي. ومن خلال هذه الدراسة توصلنا إلى أ ن للبيانات الضخمة أهمية كبيرة، وأن الدول أصبحت تتسابق للاستثمار فيها وهذا ما أبرزته جائحة كوفيد- 19 ، وأن الاقتصاد الرقمي شهد تطورا كبيرا وبالأخص في الآونة الأخيرة نظرا لتوفر التقنيات الحديثة وتطورها، وبالتالي المساهمة في التنمية الاقتصادية بشكل كبير مما جعل الدول العربة والعالمية تسعى جاهدة إلى تبني مفهوم الاقتصاد الرقمي والتحول نحو الرقمنة في جميع المجالات الاقتصادية والاجتماعية وحتى البيئية. Abstract: This study amis to introduce big data and the digital economy and develop its technologies at the regional and international level in the light of the digital revolution and the digital transformation that the world is witnessing, and to review some successful international experiences in embracing the digital economy and using big data especially in the period of the COVID-19 pandemic health crisis The study relied on the analytical descriptive approach Through. this study, we have found that big data is of great importance. This has been highlighted by the COVID-19 pandemic, and the digital economy has undergone significant development, especially in recent times due to the availability and development of modern technologies. economic development ", thus contributing significantly to economic development, making the world's waging countries strive to embrace the concept of a digital economy and to shift towards digitization in all economic, social and even environmental spheres
Big data applications and the digital economy-Highlighting Leading international experiences-
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: الاقتصاد الرقمي، البيانات الضخمة، التحول الرقمي، تكنولوجيا المعلومات; Digital Economy; Big Data; Digital Transformation; information Technology